2016
DOI: 10.1111/bjd.14325
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence rate of lentigo maligna after micrographically controlled staged surgical excision

Abstract: Staged surgical excision is superior in clearance and recurrence rates to wide local excision for lentigo maligna and should be considered as the treatment of first choice in national and international guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 14 publications
9
45
1
2
Order By: Relevance
“…21 Despite this recommendation, using 5 mm margins as in wide local excision is inadequate for many cases of LM, because clearance rates using those margins range from 24% to 70%, with recurrence rates ranging from 7% to 20%. [22][23][24][25] The mean of 9 mm margins from the marked tumor border required for clearance of LM, in our study, is consistent with a recent published literature. 26,27 Stigall et al 26 found that margins of 9 mm were needed to excise 97% of melanoma in situ.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…21 Despite this recommendation, using 5 mm margins as in wide local excision is inadequate for many cases of LM, because clearance rates using those margins range from 24% to 70%, with recurrence rates ranging from 7% to 20%. [22][23][24][25] The mean of 9 mm margins from the marked tumor border required for clearance of LM, in our study, is consistent with a recent published literature. 26,27 Stigall et al 26 found that margins of 9 mm were needed to excise 97% of melanoma in situ.…”
Section: Resultssupporting
confidence: 92%
“…The recurrence rate noted in our study of zero percent is superior to the results reported in the literature. Other staged excision procedures have a recurrence rate that varies from 0% to 12% over 14-60 months 1,19,25,[34][35][36][37]. The initial spaghetti technique for lentigo maligna in situ and acral lentiginous melanoma was reported to have a 4.76% recurrence rate over a mean follow up of 25.36 months.…”
mentioning
confidence: 99%
“…In the author's experience, skip areas have been occasionally observed but the true incidence is unknown. Overall, the rate of upstaging from LM to invasive disease upon final excision (11.7%) was high but within the expected range compared with other recently reported rates of upstaging for LM and melanoma in situ (4-11.7%) [15,[19][20][21]. Thus, the prior cosmetic treatment did not appear to have an effect on overall prognosis, but the wider surgical margins resulted in larger defects creating reconstructive challenges and increased morbidity.…”
Section: Discussionsupporting
confidence: 52%
“…2). Variations in size, number, and type of biopsy likely account for the varied rates of upstaging seen after LM diagnosis [21,[34][35][36]. This is supported by the observation that institutions performing microstaging (removal of all clinically apparent residual lesion suspicious for invasive disease prior to staged excision) achieve lowest rates of deeper residual disease (3.8%) [37].…”
Section: Discussionmentioning
confidence: 95%
“…A recent Cochrane review about interventions in melanoma in situ failed to find randomised clinical trials of surgical interventions aiming to optimise margin control (square method, perimeter technique, 'slow Mohs', staged radial sections, staged 'mapped' excisions, or Mohs micrographic surgery), which are the most widely used interventions recommended as first-line therapy [18]. A retrospective study including patients with lentigo maligna melanoma treated through staged surgery with immunohistopathological control of lateral margins showed a higher clearance and a lower recurrence rate than wide excisions [19]. A singlecenter retrospective study compared conventional surgical excision and 'slow Mohs surgery' for patients with lentigo maligna melanoma.…”
Section: Lentigo Malignamentioning
confidence: 99%